2017
DOI: 10.22159/ijcpr.2017v9i4.20762
|View full text |Cite
|
Sign up to set email alerts
|

Bioequivalence Study of Antidiabetic Activity Between Two Marketed Formulations of Metformin on Glucocorticoid-Induced Hyperglycemia in Rabbit

Abstract: Objective: Bioequivalence studies are the commonly accepted methods displaying therapeutic equivalence between two products. This study was conducted to evaluate the bioequivalence study of anti-diabetic activity between two formulations of metformin tablets which were marketed in India. Methods:In in vitro study five essential in vitro tests including disintegration, weight variation, hardness, friability and a comparative in vitro dissolution study were performed.Results: For in vivo study adult male rabbits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
Order By: Relevance
“…In the meantime, consideration should be given to how long a drug stays in each area of the GI system, especially for formulations with controlled or extended-release with a significant dissolution crossdomain [52]. Currently, the dissolution environment in vivo is frequently simulated using a single non-bio-relevant (e. g., pH 1.2, 4.5, or 6.8 buffer) or bio-relevant dissolution medium (e. g., simulated gastric or fluid), which is a practical when the majority of the drug is rapidly dissolved in a specific part of the GI tract under a particular pH condition [53,54]. The are different types of approaches, such as Noyes-Whitney modification [55], fitting data to the weibull model, using lumped parameters [56], estimation of particle size [57], direct incorporation [58], and fitting of deff scales [58] already established for incorporating dissolution in PBPK models.…”
Section: Utilizing Data From In Vitro Dissolutionmentioning
confidence: 99%
“…In the meantime, consideration should be given to how long a drug stays in each area of the GI system, especially for formulations with controlled or extended-release with a significant dissolution crossdomain [52]. Currently, the dissolution environment in vivo is frequently simulated using a single non-bio-relevant (e. g., pH 1.2, 4.5, or 6.8 buffer) or bio-relevant dissolution medium (e. g., simulated gastric or fluid), which is a practical when the majority of the drug is rapidly dissolved in a specific part of the GI tract under a particular pH condition [53,54]. The are different types of approaches, such as Noyes-Whitney modification [55], fitting data to the weibull model, using lumped parameters [56], estimation of particle size [57], direct incorporation [58], and fitting of deff scales [58] already established for incorporating dissolution in PBPK models.…”
Section: Utilizing Data From In Vitro Dissolutionmentioning
confidence: 99%
“…When we see at the structures of both, metformin ionizes in positive mode, whereas canagliflozin ionizes in negative mode. Devineni et al reported method individual estimation methods for metformin and canagliflozin [2], Attimara et al reported LC-MS method for the simultaneous determination of metformin and miglitol in human plasma: Application to pharmacokinetic studies [3], Kobuchi et al reported method for canagliflozin by LC-MS/MS [4] and many others have reported either metformin in plasma or canagliflozin in plasma [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
mentioning
confidence: 99%